﻿Trauma and allegory: truthfulness in fact and fiction. Making a private archive productive - Lars Ebert (Heritage, Memory and Conflict, 2022)
Herengracht 401 (H401), until 2019 known as Castrum Peregrini, represents the complex and intriguing history of a hermetic community of artists and scholars in Amsterdam which was formed in the years of the Nazi occupation of The Netherlands, 1940–1945.This article attempts to take stock on what we have learned in these ten years about the history of the place, as an indicator of memory politics. It also reflects on the hermeneutic gap of what we cannot know of H401’s history as we lack experiential knowledge of eyewitnesses. As the author argues below, the site of H401 shows how the ‘hermeneutic gap’ can offer a chance to make an archive, such as in the case of ‘the house on Herengracht 401’, productive and meaningful through the artistic practice of research.